STUDI PERUBAHAN PENGGUNAAN LAHAN DI KECAMATAN BAKI KABUPATEN SUKOHARJO TAHUN 2009 DAN TAHUN 2020 - Khomsah Nur Firdausi; Ahmad Ahmad; Rahning Utomowati (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
As the population of an area increases, it will be in line with infrastructure development in order to fulfill facilities for the community which will cause the need for land to also increase, while the limited nature of the land results in the change of land functions or changes in land use. This article aims to examine land use changes and patterns of land use changes in Baki District as well as factors that influence land use changes, namely population growth, accessibility and interaction of areas bordering Baki District. This study uses a qualitative type of research that uses a spatial approach with descriptive analysis of the results of overlaying land use maps and factors of land use change. Data collection in this study was carried out through secondary data analysis. image interpretation, field observations and interviews. The results of this study indicate that there has been a change in the area of ​​several types of land use, namely rice fields decreased by 101.36 hectares, while other land uses including settlements increased by 91.07 hectares, buildings increased by 6.39 hectares, and open land increased. area of ​​4.18 hectares.